Health-Compromising Behaviors Among Young Adults in the Urban Emergency Department: Opportunity for a Teachable Moment. (August 2013) - Sommers, Marilyn S.; Lyons, Michael S.; Bohn, Chad M.; Ribak, Judith H.; Fargo, Jamison D.
Emergency departments (ED) are a point of care for many young adults and may provide a teachable moment leading to behavioral change. We determined the descriptive epidemiology of health-compromising behaviors in the young adult ED population by computing demographic-adjusted estimates of prevalence and frequency of hazardous drinking, risky driving, cigarette smoking, fast-food consumption, lack of exercise, and sleep deficit. We screened 8, 815 young adults during an ED visit. Younger males had higher levels of fast-food and cigarette consumption. Non-Whites and females reported more days of little to no exercise. Whites and older individuals reported more nights of less sleep. Younger Whites reported consuming the most alcohol, with males consuming more than females. Risky driving was more frequent among younger males. Prevalence of health-compromising behaviors varied by demographics, but was higher than in the general population. Prevention strategies such as implementing a teachable moment in the ED may hold promise to reduce health-compromising behaviors.